2010
DOI: 10.1111/j.1747-0285.2010.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the In Vitro Antitumor Mechanism of Action of a New Pyranoxanthone

Abstract: Naturally occurring xanthones have been documented as having antitumor properties, with some of them presently undergoing clinical trials. In an attempt to improve the biological activities of dihydroxyxanthones, prenylation and other molecular modifications were performed. All the compounds reduced viable cell number in a leukemia cell line K‐562, with the fused xanthone 3,4‐dihydro‐12‐hydroxy‐2,2‐dimethyl‐2H,6H‐pyrano[3,2‐b]xanthen‐6‐one (5) being the most potent. The pyranoxanthone 5 was particularly effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 58 publications
0
37
0
Order By: Relevance
“…After centrifugation cells were incubated with PI (5 µg/ml) and RNase A in PBS (100 µg/ml) for 30 min on ice (Vasconcelos et al, 2000;Palmeira et al, 2010). Induced apoptosis was assayed by the Human Annexin V-FITC/PI apoptosis Kit (Bender MedSystems, Vienna, Austria) according to the manufacturer's instructions (Queiroz et al, 2011).…”
Section: Cell Cycle Distribution Analysis and Apoptosis Detectionmentioning
confidence: 99%
“…After centrifugation cells were incubated with PI (5 µg/ml) and RNase A in PBS (100 µg/ml) for 30 min on ice (Vasconcelos et al, 2000;Palmeira et al, 2010). Induced apoptosis was assayed by the Human Annexin V-FITC/PI apoptosis Kit (Bender MedSystems, Vienna, Austria) according to the manufacturer's instructions (Queiroz et al, 2011).…”
Section: Cell Cycle Distribution Analysis and Apoptosis Detectionmentioning
confidence: 99%
“…Cell proliferation was analysed with the BrdU assay, according to the protocol previously described by Palmeira et al (2010). Briefly, cells were treated for 48 h …”
Section: Cell Proliferation Analysismentioning
confidence: 99%
“…3,4-Dihydro-12-hydroxy-2,2-dimethyl-2H,6Hpyrano[3,2-b]xanthen-6-one (1) was obtained by a previously described method (Palmeira et al, 2010) and showed a purity of 98.5% by HPLC-DAD. PLGA 50:50 (M W : 50,000-75,000 Da), Pluronic ® F-68, glucose, polyvinyl alcohol (PVA), 6-coumarin, Tween ® 80 and Span ® 80 were purchased from Sigma-Aldrich Química (Sintra, Portugal) and Mygliol ® 812 was purchased from Acofarma (Coimbra, Portugal).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a dihydropyranoxanthone, synthetized by some of us, 3,4-dihydro-12-hydroxy-2,2-dimethyl-2H,6H-pyrano[3,2-b]xanthen-6-one (1, Fig. 1), presented significant antiproliferative and apoptotic inducing effects (Paiva et al, 2012;Palmeira et al, 2010) in human tumor cell lines. Both ␣-mangostin (Leão et al, 2013a) and compound 1 (Leão et al, 2013b) were shown to be promising inhibitors of p53-MDM2 interaction, with compound 1 showing the highest inhibitory activity in a yeast target-based assay, mimicking the activity of known p53 activators.…”
Section: Introductionmentioning
confidence: 99%